Response surface optimisation for the extraction of phenolics and flavonoids from a pink guava puree industrial by-product - Kong, Kin Weng; Ismail, Abdul Razak; Tan, Seok Tyug; Prasad, Krishna Murthy Nagendra; Ismail, Amin (Institute of Food Science and Technology, 2010)
Pink guava puree industry produces huge amount of by-products that have potential as sources for polyphenols. Response surface methodology was implemented to optimise the extraction conditions for phenolics (Y1) and flavonoids (Y2) from a by-product of the guava industry. A three-factor inscribed central composite design was employed to determine the effects of three independent variables, namely pH (X1: 2-6), temperature (X2: 40-60 °C) and time (X3: 1-5 h), on the response variables. The corresponding predicted values for phenolics and flavonoids were 336.30 and 427.35 mg 100 g-1, respectively. Predicted values for extraction rates of phenolics agreed well with experiment values; R2 of 0.902. However, the model derived for flavonoids extraction was less reliable; R2 of 0.983. Increase in time and temperature was found significant in increasing the extraction rate. The optimum conditions for extracting phenolics by ethanolic solvent occurred at a pH of 2 and 60 °C for a 5-h extraction.